The impact of the coronavirus (COVID-19) pandemic on elective paediatric otolaryngology outpatient services – An analysis of virtual outpatient clinics in a tertiary referral centre using the modified paediatric otolaryngology telemedicine satisfaction survey (POTSS). (November 2020) - Darr, Adnan; Senior, Andrew; Argyriou, Kalliopi; Limbrick, Jack; Nie, Huimin; Kantczak, Ada; Stephenson, Kate; Parmar, Amit; Grainger, Joe
Abstract: Introduction: Virtual outpatient clinics (VOPC) have been integrated into both paediatric and based adult outpatient services due to a multitude of factors, including increased demand for services, technological advances and rising morbidity secondary to ageing populations. The novel coronavirus disease (COVID-19) has accentuated pressures on the National Health Service (NHS) infrastructure, particularly elective services, whilst radically altering patterns of practice. Aim: To evaluate the impact of the COVID-19 pandemic on paediatric otolaryngology outpatient services whilst collating patient feedback to elicit long-term sustainability post COVID-19. Method: A retrospective analysis of VOPCs was undertaken at a tertiary paediatric referral centre over a 3-month capture period during the COVID-19 pandemic. Demographic, generic clinic (presenting complaint, new vs. follow-up, consultation type), as well as outcome data (medical or surgical intervention, discharge vs. ongoing review, onward referral, investigations, and conversion to face-to-face) was collated. Additionally a modified 15-point patient satisfaction survey was created. The Paediatric Otolaryngology Telemedicine Satisfaction survey (POTSS), was an adaptation of 4 validated patient satisfaction tools including the General Medical Council (GMC) patient questionnaire, the telehealth satisfaction scale (TESS), the telehealth usability questionnaire (TUQ), and the telemedicine satisfaction and usefulness questionnaire (TSUQ). Results: Of 514 patients reviewed virtually over a 3-month period, 225 (45%) were randomly selected to participate, of which 200 met our inclusion criteria. The most common mode of consultation was telephony (92.5%, n = 185). Non-attendance rates were reduced when compared to face-to-face clinics during an equivalent period prior to the COVID-19 pandemic. A significant proportion of patients (29% compared to 26% pre-VOPC) were discharged to primary care. Nine percent were listed for surgery compared to 19% pre-VOPC. A subsequent face-to-face appointment was required in 10% of participants. Overall, the satisfaction when assessing the doctor-patient relationship, privacy & trust, as well as consultation domains was high, with the overwhelming majority of parents' content with the future integration and participation in VOPCs. Conclusion: An evolving worldwide pandemic has accelerated the need for healthcare services to reform in order to maintain a steady flow of patients within an elective outpatient setting without compromising patient care. Solutions must be sustainable long-term to account for future disruptions, whilst accounting for evolving patient demographics. Our novel survey has demonstrated the vast potential that the integration of VOPCs can offer paediatric otolaryngology services within a carefully selected cohort of patients.